2018
DOI: 10.1017/s0033291718001575
|View full text |Cite
|
Sign up to set email alerts
|

Associations between P3a and P3b amplitudes and cognition in antipsychotic-naïve first-episode schizophrenia patients

Abstract: Our results provide further evidence for P3a/b amplitude deficits and cognitive deficits in AN-FES patients, which are neither due to antipsychotics nor to disease progress. Furthermore, our data showed significant, yet weak associations between P3b and cognition. Therefore, our data do not supply evidence for deficient P3a/b amplitudes as direct underlying factors for cognitive deficits in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
7
18
0
Order By: Relevance
“…These results, in part, agree with Mathalon et al (2000) that P3a and P3b tracked illness duration longitudinally or across different stages of illnesses (Jahshan et al, 2012a). However, when examining data longitudinally, we found that patients already showed impairment at baseline and this deficit was stable over time, similar to previous reports (del Hermens et al, 2010;Jahshan et al, 2012a;Kruiper et al, 2018;Morales-Muñoz et al, 2017). A similar pattern of results was found with P3a amplitude, suggesting P3a deficits are already present at a first episode, substantiating other reports (Brown et al, 2002;de Wilde et al, 2008;del Re et al, 2015;Demiralp et al, 2002;Devrim-Üçok et al, 2016Devrim-Üçok et al, , 2006Hirayasu et al, 1998;Kruiper et al, 2018;Morales-Muñoz et al, 2017;Renoult et al, 2007;Salisbury et al, 1998;Sumich et al, 2006;Umbricht et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results, in part, agree with Mathalon et al (2000) that P3a and P3b tracked illness duration longitudinally or across different stages of illnesses (Jahshan et al, 2012a). However, when examining data longitudinally, we found that patients already showed impairment at baseline and this deficit was stable over time, similar to previous reports (del Hermens et al, 2010;Jahshan et al, 2012a;Kruiper et al, 2018;Morales-Muñoz et al, 2017). A similar pattern of results was found with P3a amplitude, suggesting P3a deficits are already present at a first episode, substantiating other reports (Brown et al, 2002;de Wilde et al, 2008;del Re et al, 2015;Demiralp et al, 2002;Devrim-Üçok et al, 2016Devrim-Üçok et al, , 2006Hirayasu et al, 1998;Kruiper et al, 2018;Morales-Muñoz et al, 2017;Renoult et al, 2007;Salisbury et al, 1998;Sumich et al, 2006;Umbricht et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Psychopathology severity and antipsychotic medications were unrelated to P3 amplitude effect size (Polich and Jeon, 2003). Patients with first episode psychosis (FEP) and individuals at ultra high risk for psychosis also show amplitude reductions (Brown et al, 2002;de Wilde et al, 2008;del Re et al, 2015;Devrim-Üçok et al, 2006;Hirayasu et al, 1998;Kruiper et al, 2018;Morales-Muñoz et al, 2017;Renoult et al, 2007;Salisbury et al, 1998;Sumich et al, 2006;Umbricht et al, 2006;van Tricht et al, 2011). A meta-analysis of P3b found a reduction of amplitude in unaffected relatives of patients as compared to controls with a moderate pooled standardized effect size of 0.61 (Bramon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In FEP and FES subjects, as compared to HCs, different studies have highlighted a decrease of the P3b amplitude (67, 163,164,172,199,210,213,[215][216][217][218][219][220][221][222][223]. One study demonstrated that deficits in P3b, as observed for P3a, were not present at baseline, but emerged when FEP subjects were evaluated at 12-and 24month follow-up visits (166).…”
Section: P3bmentioning
confidence: 99%
“…Note that ROCFT requires a finer and longer time as a visual working memory task than CANTAB SWM, and TMT B requires more complex executive functioning using the numbers and alphabet character, compared with CANTAB IED using only simple figures. In RTI simple and five-choice reaction and movement time, there were fewer previous studies with inconsistent results in the patients [41,42]. Our RTI results suggest that the reaction and movement times of the patients were impaired in the more complex tasks than the simplified ones.…”
Section: Plos Onementioning
confidence: 47%